Higher Education Leaders' Perspectives of Student Opioid Misuse and Opioid Overdose Prevention Programs at U.S. Colleges and Universities: An Exploration of Implementation Facilitators and Barriers. - Freibott, Christina E.; Hicks, Adison; Vest, Noel; Stein, Michael D.; Shelton, Rachel C.; Lipson, Sarah Ketchen (American Journal of Health Education)
Background: Colleges and universities are well-positioned to implement opioid overdose prevention programs due to their role in supporting student health. However, implementation varies widely and is shaped by leadership decisions. Purpose: This study explored higher education leaders' perspectives on opioid misuse and overdose prevention programming using an implementation science framework. Methods: We conducted semi-structured interviews with 25 U.S. college and university leaders. Guided by the Consolidated Framework for Implementation Research (CFIR 2.0), data were analyzed using thematic coding to identify implementation barriers and facilitators. Results: Four themes emerged: (1) Reframing overdose as "poisoning" and linking prevention to mental health services increased institutional support. (2) Implementation was driven by students, faculty, and external advocacy (e.g. state policy). (3) Cross-campus and community partnerships addressed resource gaps. (4) Institutions described a phased implementation process evolving from external support to "in-house" programs offering naloxone training and overdose education. Discussion: This is the first multi-campus study to examine how institutional leaders approach overdose prevention. Results highlight a common implementation pathway and underscore the importance of shifting institutional narratives, leveraging advocacy, and fostering external and internal collaboration. Translation to Health Education Practice: Findings inform strategies for developing and sustaining overdose prevention efforts tailored to college settings. A AJHE Self-Study quiz is online for this article via the SHAPE America Online Institute (SAOI)